S132 Sputum And Bronchial Biopsy Expression Of 8-oxo-7, 8-dihydro-2'-deoxyguanosine (8-oxodg) In Asthma Is Related To Neutrophilic Inflammation And Poor Asthma Control. (10th November 2014) - Goold, DJE; Mistry, V; Singapuri, A; Cooke, M; Berair, R; Brightling, CE
Abstract : Introduction and objectives: Oxidative stress has been implicated in the pathogenesis of asthma. Validated sputum biomarkers are required to assess this and its relationship to other clinical variables. We sought to compare sputum and bronchial 8-oxodG expression in asthma and health; assess the sputum repeatability; and explore its relationship with induced sputum inflammatory cells counts and exacerbations. Methods: Asthmatics and healthy controls were recruited from a single centre and underwent clinical characterisation including sputum induction (asthma n = 58, health n = 27) and bronchial biopsy (asthma n = 16, health n = 10). Sputum and epithelial 8-oxodG expression was measured by ELISA and Immunohistochemistry respectively. Sputum asthmatics were assessed at a repeat stable visit at 6 months. Results: Between health and asthma, there were no significant differences in the median (IQR) sputum 8-oxodG levels [12 (16) ngml -1 vs. 11 (15) ngml -1, p = 0.36] or the mean (SEM) percentage area of epithelium reaching threshold intensity for 8-oxodG [2.0 (0.7)% vs. 4.4 (1.0) %, p = 0.12]. Asthma sputum 8-oxodG correlated with the sputum total cell count ( r s =0.53, p < 0.01), sputum neutrophils ( r s =0.27, p = 0.04), sputum macrophages ( r s =-0.31, p = 0.02) and serum IgE ( r s =-0.27, p = 0.04). Epithelial 8-oxodG correlated to the number of exacerbations in the previous year (rs =0.70, p < 0.01) and the ACQ 6 (rs =-0.52, p = 0.04). The upper 95th confidence interval of sputum 8-oxodG and epithelium 8-oxodG reaching threshold in healthy controls was used to split asthma patients into 8-oxodG high and low groups. The sputum 8-oxodG high group (n = 13) had significantly higher sputum total cells 8.08 [8.41] x10 6 g -1 vs. 2.25 [2.91] x10 6 g -1, p < 0.01, higher sputum neutrophils (82.25[32.75]% vs. 55.50 [29.75]%, p < 0.01) and lower serum IgE (30 [76.50] KUL -1 vs. 157 [212.90] KUL -1, p < 0.01). The epithelial 8-oxodG high group (n = 8) had significantly more exacerbations 3.9 (0.3) vs. 0.5 (0.3) p < 0.01 and a lower ACQ 6 score 1.4 (0.3) vs. 2.4 (0.3) p = 0.04. In the asthmatic group, the intra-class correlation coefficient of sputum 8-oxodG between the 2 visits was 0.51 (p < 0.01). Conclusions: 8-oxodG expression in sputum and bronchial biopsies was not different between asthma and health, although we did identify an 8-oxodG high group in asthma. Interestingly, expression in asthma was associated with neutrophilic inflammation and poor asthma control.